PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP PENGUNGKAPAN EMISI KARBON - Ursula Sinawang Trufvisa; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2019)
This study aims to obtain empirical evidence and analyze the effect of board of commissioner’s characteristics on carbon emission disclosure. Board of commissioner characteristics that are used in this study are board of commissioner size, composition of independent commissioner, gender diversity and nationality diversity on board of commissioner. The population in this study is manufacturing companies listed on Indonesia Stock Exchange during 2013-2017. There are 160  research samples that are used based on predefined criteria. Data analysis using descriptive statistical analysis, classical assumption test, and panel data regression. The results of the analysis show that board of commissioner’s characteristics such as composition of independent commissioner have a positive and significant effect on carbon emission disclosure. In addition, board of commissioner size, and nationality diversity on board of commissioner have positively but insignificant effect on carbon emission disclosure. While gender diversity on board of commissioner have negatively and insignificant effect on carbon emission disclosure.